Discovery of Kasugamycin as a Potent Inhibitor of Glycoside Hydrolase Family 18 Chitinases - Qi, Huitang; Jiang, Xi; Ding, Yi; Liu, Tian; Yang, Qing (Frontiers in Molecular Biosciences, 2021)
Kasugamycin, a well-known aminoglycoside antibiotic, has been used widely in agriculture and medicine to combat microbial pathogens by binding the ribosome to inhibit translation. Here, kasugamycin was discovered to be a competitive inhibitor of glycoside hydrolase family 18 (GH18) chitinases from three different organisms (bacterium, insect and human). Results from tryptophan fluorescence spectroscopy and molecular docking revealed that kasugamycin binds to the substrate-binding clefts in a similar mode as the substrate. An electrostatic interaction between the amino group of kasugamycin and the carboxyl group of a conserved aspartate in GH18 chitinase (one of the catalytic triad residues) was found to be vital for the inhibitory activity. This paper not only reports new molecular targets of kasugamycin, but also expands our thinking about GH inhibitor design by using a scaffold unrelated to the substrate.